2010
DOI: 10.1007/bf03392201
|View full text |Cite
|
Sign up to set email alerts
|

Come on in, the water is fine: Achieving mainstream relevance through integration with primary medical care

Abstract: Behavior analysis is a generic science, and Skinner's vision for it was that it would become a mainstream force, relevant for most if not all human concerns, major and minor. Clearly his vision has not been realized. Determining why this is the case would require a complex multifactorial analysis. One likely factor is that the majority of its basic science findings have been obtained from the study of rats and pigeons. Another likely factor, one directly addressed by this paper, is that the majority of its app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 46 publications
1
65
0
1
Order By: Relevance
“…Given that there was a preexisting history with behavior science and behavioral medicine, it seems like an obvious opportunity for such partnership. Furthermore, it may behoove behavior analysts to use common terminology in publishing outside of BA journals, while still maintaining the integrity of the procedures and principles (Friman, 2010). It is also important to engage in flexibility with regard to the type of research design selected when collaborating with researchers in other disciplines who may be unfamiliar with or not value the utility of single-subject research.…”
Section: Re-integration Of Behavioral Medicine With Applied Behavior mentioning
confidence: 99%
See 2 more Smart Citations
“…Given that there was a preexisting history with behavior science and behavioral medicine, it seems like an obvious opportunity for such partnership. Furthermore, it may behoove behavior analysts to use common terminology in publishing outside of BA journals, while still maintaining the integrity of the procedures and principles (Friman, 2010). It is also important to engage in flexibility with regard to the type of research design selected when collaborating with researchers in other disciplines who may be unfamiliar with or not value the utility of single-subject research.…”
Section: Re-integration Of Behavioral Medicine With Applied Behavior mentioning
confidence: 99%
“…The contribution of behavior analysis to the field of autism and developmental disabilities is profound and undeniable, and should not be minimized. However, in order to achieve Skinner's early vision of mainstream prominence, a demonstration of mainstream relevance is needed, therefore mandating a need for ABA to diversify areas of contribution (Friman, 2010). Some of the work in ABA could be categorized as behavioral medicine, especially given our analysis of environmental conditions being used to address biological functions of the organism.…”
Section: Re-integration Of Behavioral Medicine With Applied Behavior mentioning
confidence: 99%
See 1 more Smart Citation
“…As Poling (2010) concluded, the science of behavior can be widely applied outside of the field of developmental disabilities, and strengthening alternative connections will ensure the survival and prosperity of the field as a whole. Friman (2010) suggested that one way to ensure relevance may be to enter the mainstream through integration into an already existing field. Integration may not be easy to achieve, but pushing the boundaries of behavior analysis will surely increase the long-term strength and viability of the field (Vyse 2013).…”
Section: Reconnecting Zoos Aquariums and Behavior Analysismentioning
confidence: 99%
“…In fact, this trend began with the last issue under Mike Dougher's editorship with a special section edited by me and titled ''The Future of Behavior Analysis.'' That section contained articles by Friman (2010), Poling (2010), andPalmer (2010) with an introduction by me (Schlinger, 2010), in which I noted that some of the concerns expressed by the authors, related to both the experimental and applied domains, had potentially serious consequences for the future of our field. That section was successful in that it spurred debate, having been cited by several subsequent papers in TBA over the past 3 years, including some in the current issue.…”
mentioning
confidence: 99%